Analysis and proposal of energy planning and renewable energy plans in South America: Case study of Ecuador. (January 2022) - Icaza, Daniel; Borge-Diez, David; Galindo, Santiago Pulla
Abstract: This research evaluates the South American Electric Energy System and its features related to the inclusion of renewable energies into the transition processes to leave fossil fuel-based energy systems behind. Analysis of the Ecuadorian case is a novel approach because in the first instance its matrix was based on the use of fossil fuels, with dire consequences of pollution, especially in the Amazon. Interest is growing in terms of economic, legal and social renewal, leaving behind the rapidly depleting oil systems which have been a polluting source. This research presents a novel analysis of the state of the Ecuadorian electricity system and after a flexible analysis in Energyplan, proposes the feasible renewable energy sources and their shares to guarantee the new demand in 2050 and an Ecuadorian 100% renewable electricity generation system, having a positive impact on the monetary, increasing production levels and improving the quality of life of its citizens. Installed power by 2050 is expected to be 20 GW and will require an annual production of 72.24 TWh. Hydro (6.02 GW), solar PV (5.7 GW) and wind (5.61 GW) will have the most impact on the Ecuadorian energy matrix. The average production cost of 1 MWh will be approximately 18 US cents. Graphical abstract: Image 1